Vapor–liquid equilibria for ethyl acetate + methanol and ethyl acetate + ethanol mixtures: Experimental verification and prediction - Gomes, Cícero Sena Moreira (2014)
This work aims of the determination of a series of vapor–liquid equilibrium (VLE) experimental data at low pressure (70 kPa) for binary mixtures of ethyl acetate with methanol and ethanol. The Fischer’s ebulliometer was used for the measurements of VLE data. A complete series of equilibrium data was obtained such as pressure, temperature and compositions of the liquid and vapor phases (PTxy). The two VLE data sets were submitted to a thermodynamic consistence test, where the deviations were evaluated in all variables, using the UNIQUAC activity coefficient equation. The magnitude of the average deviations was within the experimental uncertainty satisfying the Gibbs–Duhen equation. The data sets were also used to test the prediction of the UNIFAC model in its original and modified editions and the results were also within experimental uncertainties. Then a series of binary systems containing alcohols (methanol and ethanol) and esters (methyl and ethyl acetate) were collected from the literature for testing systematically the capability of the UNIFAC contribution method for this type of mixtures